High-yield and Functional IgY Anti-S1 SARS-CoV-2 Delta Variant from Chicken Immunized with In-house Recombinant Protein - Kamaluddin Zarkasie; Teridah Ernala Ginting; Andrea Hynan Poeloengan; Febi Andriani; Aksar Chair Lages; Vina Cornelia; Anggah Nugraha; Bustanur Rosidi; Setyarina Indrasari; Chairul Anwar Nidom; Irawan Yusuf (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: During COVID-19 pandemic, effective preventive and therapeutic strategies was urgently necessary, especially with the emerging Delta variants. Previous existing interventions have some limitations, and passive immunization using immunoglobulin Y (IgY) is considered viable. However, the potential of IgY antibodies remains underexplored locally. Therefore, a feasible study was conducted to produce IgY against the SARS-CoV-2 Delta variant from chickens raised on a farm, instead of a laboratory environment, by using in-house recombinant protein, to offer a promising low-cost alternative for passive immunization.METHODS: In-house HEK293 cell line was produced by secreting recombinant S1 subunit protein of SARS-CoV-2 Delta variant. The protein was confirmed by western blot and used as an immunogen in two chickens. IgY was extracted from egg yolks. Titers and neutralization activity of IgY against SARS-CoV-2 Delta variant were confirmed by enzyme-linked immunosorbent assay (ELISA) and surrogate virus neutralization test (sVNT). The functionality of IgY was then tested on lysates from COVID-19 patients' nasopharyngeal swabs with dot blot method.RESULTS: The high anti-S1 IgY titers and neutralization activity was confirmed following immunization with 1 mg immunogen at 2–3-week intervals. IgY titers varied between chickens and time points. The mean titers showed significant increase after the fifth immunization (1.21, 1.72 and 1.48; with p<0.05 for all). Neutralization activity appeared after the second immunization and was significant after the third immunization (31.9%, 34.95%, 26.9%, 47.6%, 54.95% and 57.3%; with p<0.05 for all). The results of this study showed that the extracted IgY reacted to COVID-19 patients' nasopharyngeal swabs lysates.CONCLUSION: A high-yield and functional IgY anti-S1 SARS-CoV-2 Delta variant can be produced from chicken immunized with an in-house recombinant protein. This can be an alternative for affordable and effective IgY production during public health emergencies.KEYWORDS: IgY, SARS-CoV-2, S1 subunit protein, egg yolk, chicken